Penguatan Kapasitas Kelompok Nelayan Wirausaha Mandiri melalui Transfer Teknologi Tepat Guna - Ermayanti Ishak; Roslindah Daeng Siang (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2015)
Processing of target species do not optimal, especially the processing of the by-catch product. This is caused by the weak capacity of the fishing groups, particularly in the utilization of marine products in the dry season and the acquisition of market information, so it requires increased knowledge and transferal appropriate technology. Purpose of the study: (1) generate a group of fishermen who are skilled, creative and innovative in the processing of marine products; (2) create a group of fishermen who are good entrepreneurs with venture capital is cheap, affordable and sustainable; (3) make the fishing village groups as independent business pioneer advanced and community known as a producer and marketer of processed fish products as one of the typical souvenir of Kendari. Method of determining the sample was done by purposive sampling. This activity involves two groups of partners consisting of fishermen processors groups and fishermen fishing groups each of 20 people. The data were analyzed descriptively of the results of the implementation of the two activities, namely non-physical activities (socialization and education) and physical activity (manufacture plots hygienic drying fish and puffer fish burger-making). Action research results make a positive contribution to the strengthening of the capacity of a group of fishermen in the economic, scientific, cultural and social skills. Another positive contribution is opening insights and ways of thinking to make use of by-catch product into marketable products and process raw materials of marine fish with a hygienic manner that supports the improvement of the quality of the product to be accepted in the market, and create jobs in the village with the ability of a group of fishermen in entrepreneurship independent, which in turn can improve the economics of fishing households and assist the government in the construction of coastal villages.